FACEBOOK® GROUP USAGE TO SUPPORT FLIPPED-CLASSROOM LEARNING ON OCULAR TRAUMA - Muhamad Reza Utama; Deny Yuliawan; Yoyo Suhoyo; Widyandana Doni (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Facebook has been acknowledged as an alternative media in supporting traditional learning activities. However, its potential in enhancing students' cognitive engagement on flipped-classroom' activities is still not much known. This study aims to measure undergraduate medical students' cognitive engagement changes after joining an ocular trauma flipped-classroom' Facebook group. Methods: This pre-experimental study was involving 45 third-year undergraduate medical students of Muhammadiyah Surabaya' University who were joining the ocular trauma flipped-classroom' Facebook group. Three cognitive engagement variables were measured before students were joining the group and after the flipped-classroom' face to face session ended. Finally, metrics data of the group members' activities, which had been collected using Facebook Insight, used to shown changes between the active and passive user. Results: All users' (n = 45) cognitive engagement were rising significantly after join the Facebook group (motivation, p = 0,000; self-directed learning readiness, p = 0,000; knowledge towards ocular trauma topic, p = 0,000). Increase in average active user knowledge was 11.09 points higher than passive users. Self-efficacy aspect of the students' learning motivation and self-management aspects of the students' self-directed learning readiness were the most increased sub-components. Conclusion: Facebook group has the potential to improve students' cognitive engagement on ocular trauma' flipped classroom.